2013
DOI: 10.1111/cod.12084
|View full text |Cite
|
Sign up to set email alerts
|

A case of anaphylaxis caused by polyethylene glycol analogues

Abstract: PEGs and polysorbates are found in many pharmaceuticals, cosmetics, and foods (1, 2). We report the first patient with anaphylaxis caused by PEGs and polysorbate 80 that were cross-reactive with hydroxyethyl starch.A 33-year-old man had undergone surgery for lumbar disc herniation. He went into anaphylactic shock a few minutes after the application of povidone-iodine gel to the dead space resulting from the surgery. He was successfully treated with intravenous corticosteroids and adrenaline. He reported a hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 5 publications
1
38
0
Order By: Relevance
“…Our case supports the assumption of cross-reactivity between PEGs of different molecular weights and polyethylene glycol analogues [7, 8]. Like other authors have previously shown, the positive intradermal test suggests an IgE-dependent mechanism, although no control tests were performed on healthy individuals to rule out unspecific reactivity [9].…”
Section: Discussionsupporting
confidence: 89%
“…Our case supports the assumption of cross-reactivity between PEGs of different molecular weights and polyethylene glycol analogues [7, 8]. Like other authors have previously shown, the positive intradermal test suggests an IgE-dependent mechanism, although no control tests were performed on healthy individuals to rule out unspecific reactivity [9].…”
Section: Discussionsupporting
confidence: 89%
“…Polymerization and molecular structure of polyethylene glycol ( PEG ) and PEG derivatives. Two chemical moieties, –( OCH 2 CH 2 )‐ and – OCH 2 CH 2 OH , are shared by both PEG s and some PEG derivatives, making cross‐sensitization theoretically possible .…”
Section: Background On Polyethylene Glycolsmentioning
confidence: 99%
“…Symptoms associated with immediate‐type PEG hypersensitivity were often severe and rapid in onset. Of the 37 cases identified, 28 (76%) described HSRs that fulfilled criteria for anaphylaxis . Common manifestations were pruritus, tingling, flushing, urticaria, angioedema, hypotension and bronchospasm.…”
Section: Literature Review Of Immediate‐type Hypersensitivity To Pegsmentioning
confidence: 99%
“…Cross-reactivity with macrogol analogies, as in this case, macrogol 6000 and polysorbate 80 (a macrogol-derivative), has been reported 8 . Clinical allergy may also be dependent on both dose and route of administration.…”
mentioning
confidence: 92%
“…1b). Finally, since cross-reactivity has been suggested in the literature 8 , prick testing with polysorbate 20, polysorbate 80 and povidone were done; polysorbate 80 was positive (weal diameter 6mm, histamine weal 5-mm). Intradermal testing or oral challenge was not done for safety reasons, as systemic anaphylactic reactions have been reported following similar testing 4 .…”
mentioning
confidence: 99%